Rich microbial communities inhabit water treatment biofilters and are differentially affected by filter type and sampling depth - Wakelin, S.A.; Page, D.W.; Pavelic, Paul; Gregg, A.L.; Dillon, P.J. (IWA Publishing, 2010)
Factors affecting microbial diversity (richness) and community structure in biofilter columns were investigated. At a pilot filtration plant, granular activated carbon (GAC), anthracite and sand-based filters were used to treat stormwater from an urban catchment. After 12 weeks operation, sand media filters clogged (hydraulic conductivity declining by 90%) and all filters were destructively sampled. All biofilters had similar levels of polysaccharide in the surface layer, however only the sand columns clogged. This clogging may have been due to a combination of polysaccharide and small particle size, the development of a sand-specific microbial community, or other biogeochemical interactions. DNA fingerprinting was used to show that bacterial, archaeal and eukaryotic communities were present in all filter types and at all sampling depths (to 45 cm). The bacterial community was far richer (Margalefs index, d, 1.5-2) than the other groups. This was consistent across filter types and sampling depths. The structure of the bacteria and archaea communities in sand filters differed to those in GAC and anthracite filters (P<0.05). In contrast, eukaryotic communities were similar in surface biofilm layers, irrespective of filter type. As such, physicochemical properties of filters differentially influence the microbial community. Furthermore, we have established that archaea are distributed throughout biofilters; the role of these microorganisms in water treatment and filter function, particularly clogging, requires attention.